PARTISIPASI MASYARAKAT PEDULI API DALAM PENANGGULANGAN KEBAKARAN HUTAN DAN LAHAN (Studi Kasus di Kecamatan Bunut Kabupaten Pelalawan Tahun 2010-2013) - Deo Sayendri; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study was conducted to describe the forms of participation of the Community Care Fire (MPA) which has been formed in accordance Bunut Head Decree (SK) issued Head Bunut. As for the background of this research is not maximal MPA performance of the well. This study uses the theory that emphasizes community participation Cohen and Uphoff approach in order to explain the phenomena encountered in the field. This study used qualitative methods, while the technique of collecting data using interviews, observation and discussion with sources of research. Furthermore, the data in the form of data qualitative and quantitative data were analyzed with descriptive data analysis techniques.The results showed that the group Concerned Citizens Fire as important actors in society in implementing land and forest fire prevention have not been able to carry out their duties properly due to lack of facilities and the seriousness of Community Care in a fire that had been expected to participate according to Head Bunut. Moreover, many people who do not know or have not been the emergence of public awareness of the impact of the burning of land and forests. So that this condition makes a lot of land and forest fires occurred in the District Bunut.The results also show that the social scope of the interaction between society, business and government have not been established. This of course have an impact on the political scope of public support for participation. While the scope of the economy also declined due to the impact of forest and land fires.Keywords: Community Participation, Community Groups Concerned Fire, Land and Forest Fires.